The Development of Natural and Cultural Tourism in Buku Limau Island Based on Social Networking - Putra Pratama Saputra; Novyandra Ilham Bahtera; Laila Hayati (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
The local authorities are promoting Buku Limau Island as an emerging tourist site. The island's distinguishing features include stunning coral reefs, picturesque white sandy beaches, and its role as a hub for the production of salted and fresh seafood. The objective of this study is to identify and describe the natural and cultural attractions on Buku Limau Island, particularly in the Manggar Subdistrict of East Belitung Regency. Additionally, the study seeks to examine social networks in order to facilitate the development and expansion of natural and cultural tourism destinations in the area. This research employs a mixed-method approach, utilizing data gathering approaches such as observation, focus group discussions (FGD), and surveys administered through questionnaires. UCINET program was used to conduct descriptive qualitative analysis and social network analysis to identify and reveal tourist characteristics. This is followed by the breakdown and study of social networks among stakeholders and interest groups. The findings of this study indicate that Buku Limau Island exhibits attributes of both natural and cultural tourism, with the predominant population of fishermen being of Bugis ethnicity. The identification and study of social networks demonstrate that stakeholders have formed networks to actively support and cultivate tourism attractions, encompassing both natural and cultural aspects. Nevertheless, there are still certain stakeholders who have not been engaged in the network throughout the process of developing and improving the tourism destination.  The research limits are deliberately established to enhance the study's focus and depth. The information and data acquired are directly relevant to the fundamental issue of this investigation. The scope of this study is limited to the creation of natural and cultural tourism centered around social networks on Buku Limau Island. Theoretical implications shed light on the ideas of local government assistance, social networks, and tourist attractions. Meanwhile, the practical consequences surely affect the government, tourism stakeholders, and the community in their efforts to promote the growth of natural and cultural tourism through social networks on Buku Limau Island.